The epidemiology of peste des petits ruminants in Pakistan and possible control policies - Hussain, M.; Afzal, M.; Ali, Q.; Taylor, W.; Mariner, Jeffrey C.; Roeder, P. (2008)
Peste des petits ruminants made its first clinical appearance in Pakistan during an epidemic in Punjab Province in 1991, but its level of activity in subsequent years was never systematically recorded. In 2003, 2004 and 2005 teams trained in participatory disease surveillance methods visited a large number of villages throughout Pakistan to record the prevalence and impact of key livestock diseases. Peste des petits ruminants has emerged from their study as a common and economically damaging disease of small ruminants within the country, appearing to be endemic in the north of Punjab and epidemic in Azad Jammu and Kashmir, and Sindh during the study period. It should be possible to reduce the incidence level using a combination of zoosanitary measures and the intensive use of vaccine.